1994
DOI: 10.1177/036354659402200509
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction Using the Semitendinosus and Gracilis Tendons Augmented by the Losee Iliotibial Band Tenodesis

Abstract: Seventy patients were evaluated after combined intra- and extraarticular reconstruction of the anterior cruciate ligament. Semitendinosus and gracilis tendons were used for the intraarticular reconstruction and Losee iliotibial band tenodesis for the extraarticular procedure. Minimum followup was 5 years (average, 7). Clinical examination and instrumented ligament examination with the KT-1000 arthrometer and the Cybex II dynamometer were used to evaluate results. Subjectively, patients had no complaints of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 62 publications
1
36
0
Order By: Relevance
“…In this study, experimental testing of a screw tibial fixation for hamstrings tendons has been performed. This device is designed for four-strand grafts; this surgical technique has being gaining ground on bone-tendon-bone procedures because of its low morbidity and good results [2-4], although two-bundle grafts have demonstrated to achieve enough stability [16]. Bio-absorbable screws have evident advantages [8]: they provide similar or even better fixation than metallic screws [17-20], causing less damage to the graft [21] and without interfering with the graft incorporation process [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, experimental testing of a screw tibial fixation for hamstrings tendons has been performed. This device is designed for four-strand grafts; this surgical technique has being gaining ground on bone-tendon-bone procedures because of its low morbidity and good results [2-4], although two-bundle grafts have demonstrated to achieve enough stability [16]. Bio-absorbable screws have evident advantages [8]: they provide similar or even better fixation than metallic screws [17-20], causing less damage to the graft [21] and without interfering with the graft incorporation process [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the use of double looped hamstrings has been growing in popularity among arthroscopists. Excellent results have been reported with this technique [2,3], without significant differences between the outcomes of both procedures [4]. …”
Section: Introductionmentioning
confidence: 99%
“…Randomized, controlled trials have previously demonstrated the superiority of reconstruction compared with primary repair [1][2][3] . Additional randomized, controlled trials have shown no clinical differences in outcome between the use of patellar tendon autograft and the use of hamstring tendon graft [4][5][6][7][8][9][10][11] or between one and two-incision arthroscopic operative techniques 10,[12][13][14] . Thus, reconstructions of the anterior cruciate ligament have been performed to allow patients to resume activities, especially in sports requiring cutting and pivoting, and studies have shown overall good short-term function 15,16 .…”
mentioning
confidence: 99%
“…Despite these advantages, a considerable decrease in knee fl exion strength during deep knee fl exion has been reported after harvesting the ST tendon for ACL reconstruction (Nakajima et al 1996 ;Ohkoshi et al 1998 ;Tadokoro et al 2004 ;Tashiro et al 2003 ), although the peak knee fl exion torque of the ST tendon-harvested limb can eventually recover to at least 90 % of normal (Aglietti et al , 1997Anderson et al 1994Anderson et al , 2001Cooley et al 2001 ;Cross et al 1992 ;Ferretti et al 2002 ;Gobbi et al 2003 ;Irie and Tomatsu 2002 ;Karlson et al 1994 ;Lipscomb et al 1982 ;Lipscomb and Anderson 1986 ;Maeda et al 1996 ;Siegel and Barber-Westin 1998 ;Simonian et al 1997 ;Yasuda et al 1995 ). There are many advantages of using the ST tendon, including ease of harvest during ACL reconstructive surgery, suitable morphology for use as an ACL graft, and lower donor-site morbidity .…”
Section: Introductionmentioning
confidence: 99%